Caracterización Faneróptica de la Población Equina en la Caballeria de Sangre Nro. 7 Cazadores de los Ríos en la provincia de Loja, Ecuador - Silva Solórzano, Ana Cristina (2017)
The objective of the present work was to characterize phaneroptically the horses of the blood Cavalry No. 7 "Cazadores de los Rios", the population consisted of 18 animals 8 females and 10 males. The characterization was made based on the following variables:hair color, hair direction, pigmentary patterns, numbers of moles, Head cephalic, lumbar back, anterior and posterior leaflet, anterior and posterior helmet, Fanoptic of the tail, Cephalic profile and lumbar back profile. For the study we calculated average and tables of absolute and relative frequencies for each of the variables and the statistical analysis was performed using the chi-square test (x²) through the GLIMMIX SAS procedure. The predominant phaneroptic characteristics were: brown hair color with a frequency of 66.7%, pigmented eumelanic fire pattern with 50%, 61.1% didn’t present moles, With respect to the lumbar dorso photoroptic, animals with no characteristic with 55.6%And finally the predominant color of the tail was black with a frequency of 66.7%, concluding that the characteristics of horses of blood cavalry N ° 7 "Cazadores de los Rios" are similar to purebred English thoroughbred horses. KEYWORDS:Phaneroptic, glimmix, eumelanic.